Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1051/0004-6361/202040073
|View full text |Cite
|
Sign up to set email alerts
|

Distance and extinction to the Milky Way spiral arms along the Galactic centre line of sight

Abstract: Context. The position of the Sun inside the disc of the Milky Way significantly hampers the study of the spiral arm structure given the high amount of dust and gas along the line of sight, and the overall structure of this disc has therefore not yet been fully characterised. Aims. We aim to analyse the spiral arms in the line of sight towards the Galactic centre (GC) in order to determine their distance, extinction, and stellar population. Methods. We use the GALACTICNUCLEUS survey, a JHKs high-angular-resolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

7
3

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…We notice that in the Spiral model the Sun is correctly placed in the inter-arm region between Sagittarius-Carina and Perseus arms. In this model, the distance to the closest spiral arm, in the direction of the Galactic center, is about 1.5 kpc, well compatible with recent determinations, as e.g., [70].…”
Section: Modelsupporting
confidence: 91%
“…We notice that in the Spiral model the Sun is correctly placed in the inter-arm region between Sagittarius-Carina and Perseus arms. In this model, the distance to the closest spiral arm, in the direction of the Galactic center, is about 1.5 kpc, well compatible with recent determinations, as e.g., [70].…”
Section: Modelsupporting
confidence: 91%
“…Here we consider the P17 model with Ω p = 37.5 km s −1 kpc −1 which was found to be a good match to the VIRAC proper motions in Clarke et al (2019) and, with gas dynamical modelling, to the observed distribution of interstellar gas in the (𝑙, 𝑣 los )-diagram (Sormani et al 2015;Li et al 2016Li et al , 2021. We neglect spiral arms in the Galactic Disc, which contain too few stars to have a significant impact on the normalised kinematic histograms used in our fitting procedure (Nogueras-Lara et al 2021b).…”
Section: Calculation Of 𝑝(𝑜mentioning
confidence: 99%
“…Here we consider the P17 model with Ω p = 37.5 km s −1 kpc −1 which is a good match to the VIRAC proper motions (Clarke et al 2019) and, with gas dynamical modelling, to the observed distribution of interstellar gas in the (𝑙, 𝑣 los )-diagram (Sormani et al 2015;Li et al 2016Li et al , 2021. We neglect spiral arms in the Galactic Disc, which contain too few stars to have a significant impact on the normalised kinematic histograms used in our fitting procedure (Nogueras-Lara et al 2021b).…”
Section: Calculation Of 𝑝(𝑜mentioning
confidence: 99%